The Quality of Life of Patients after Conservative Treatment of Adolescent Idiopathic Scoliosis - Levytskyi, A.F.; Burianov, O.A.; Benzar, I.M.; Omelchenko, T.M.; Ovdii, M.O. (TERRA ORTHOPAEDICA, 2022)
Summary. Relevance. Health-related quality of life (HRQoL) is an important indicator of the treatment. Quality of life consists of functional, physical, emotional, social and spiritual states [1], and therefore has become a leading criterion in many researches, along with physical and economic factors. In the course of its development, the concept of quality of life has been correctly indicated as a parameter of the result in the recommendations of many medical societies [2].Objective: to assess the quality of life of patients with adolescent idiopathic scoliosis who were treated conservatively.Materials and Methods. The study included 54 patients who were treated at the clinic of the Department of Pediatric Surgery of the Bogomolets National Medical University in the period from 2015 to 2019. The mean age of the patients was 12.6 years (range 10 to 15 years), the mean Cobb angle was 24.8° (range 20° to 37°), and the mean torso angle was 7.2° (range 6° to 17°). All patients underwent conservative treatment with continuous use of the Cheneau corset [6]. Indicators of quality of life were studied using Brace Questionnaire (BrQ) [8] at the beginning and at the end of treatment. The minimum duration of conservative treatment was 2 years.Results. Patients with adolescent idiopathic scoliosis at the end of treatment had lower scores in all domains of BrQ. This difference was statistically significant for the mean overall BrQ score and for the domains of general health perception, physical functioning, emotional functioning, self esteem and aesthetics, bodily pain, and social functioning. Assessments in the domains of vitality and school activity were not significant.Conclusions. It was found that the quality of life immediately after the end of conservative treatment of adolescent idiopathic scoliosis in the Cheneau сorset is gradually improving. Due to limitations in the design of the study, this finding highlights the importance of measuring quality of life indicators to assess how patients with adolescent idiopathic scoliosis perceive the impact of their disease.